THE EFFECTS OF CINNAMON POWDER AND SODIUM BENZOATE ON THE PRESERVATION OF ORANGES - Faris Maulana, Kaysan; Erni Purnasari; Elisa (Perhimpunan Ahli Epidemiologi Indonesia, 2025)
Background: Oranges (Citrus sinensis) are highly perishable fruits. Their preservation is of interest due to the global importance of reducing food spoilage. Cinnamon powder, a natural preservative, and sodium benzoate, a synthetic one, are both used in food preservation, yet their comparative efficacy in maintaining fruit quality is unclear. Methods: A controlled laboratory experiment was conducted using 5 groups of oranges subjected to 0.1% and 0.3% concentrations of cinnamon powder and sodium benzoate, and a control group. Parameters measured included mass change and pH stability over a 5-day refrigerated period. Quantitative data were collected daily, and statistical observations were made on moisture retention and pH changes. Results: Cinnamon powder (especially at 0.3%) showed the highest effectiveness in preserving fruit mass, with mean mass increases of 15.128% (0.1%) and 21.664% (0.3%). Sodium benzoate, by contrast, showed modest increase (5.542%) at 0.1% but a decrease (-1.966%) at 0.3%. pH levels across all samples remained relatively stable (4-5), indicating that neither preservative caused significant acidification. Conclusion: Cinnamon powder, especially at higher concentrations, is more effective in preserving the moisture content of oranges compared to sodium benzoate. Sodium benzoate was slightly more consistent in maintaining pH but failed to prevent mass loss at higher concentrations.